Corporate legacy debt, inflation, and the efficacy of monetary policy - Charles A. E. Goodhart; M. Udara Peiris; Dimitrios P. Tsomocos; Xuan Wang (Tinbergen Institute, 2024)
We investigate how corporate legacy debt, through heterogeneous household portfolios, affects monetary policy's ability to control inflation. We find that (1) corporate debt generates an income effect that counters the traditional substitution effect, reducing the effectiveness of rate changes on inflation; (2) higher corporate debt exacerbates the trade-off between output and inflation stabilization. The income is positive on aggregate demand and inflation despite declining output. Local projections using U.S. monetary policy shocks show that over six quarters the cumulative difference in output and inflation for high and low corporate debt-to-household asset ratios is 3 percent and 1.2 percent.
Keywords: E31; E32; E52; G11; G51; 330; Household heterogeneity; Inflation; Monetary policy; Corporate debt; Giffen good